One and Done, or a Bundle and Stumble? An Exploration of Assessment Methods in Undergraduate Science Curricula - Edwards Shelley (Sciendo, 2022)
Introduction: Assessment, historically, has been done in a summative manner in post-secondary education (HE). Whilst useful for the purposes of grading and assessment of competency, there is also increasing pressure from post-secondary education institutions to meet certain standards in terms of education quality and graduate numbers, putting pressure on teachers to produce evidence of students' level of understanding and thus putting a greater emphasis on the use of summative assessments. The formative assessment approach for student learning is preferable in some fields, but how useful is this format for the science subjects?